Separation of xylose from glucose-xylose solution using ion exchange resins - Mohammad Aizzat, Nawi (2013)
In this present study 5 different types of ion-exchange resins were used to separate xylose from glucose-xylose mixture. The resins were strong base cation (SBC), strong acid cation (SAC) and weak acidic cation (WAC) with same ion forms of H+. Glucose and xylose were measured using single-component isotherms and being measured at 20oC, 30oC and 40oC. The concentration of the glucose-xylose mixtures are 0.5g/L, 1.0g/L and 1.5g/L. The composition of mixture of glucose-xylose also being varies 1:1, 1:9 and 9:1. The entire sample is being tested at different rotation speeds which are 110rpm, 160rpm and 210rpm. The wavelength is set at 620nm for this experiment. All the data obtained from 5 different resins were described in linear isotherms. The result of each resins were compared based on their adsorption capabilities towards those sugar. From the result gathered, Dowex M-31 shows highest separation of glucose from the glucose-xylose mixture. The optimum temperature and rotation is 30oC and 160rpm respectively.